Exosomes, MDSCs and Tregs: A new frontier for GVHD prevention and treatment - Hess, Nicholas J.; Kink, John A.; Hematti, Peiman (Frontiers in Immunology, 2023)
The development of graft versus host disease (GVHD) represents a long-standing complication of allogeneic hematopoietic cell transplantation (allo-HCT). Different approaches have been used to control the development of GVHD with most relying on variations of chemotherapy drugs to eliminate allo-reactive T cells. While these approaches have proven effective, it is generally accepted that safer, and less toxic GVHD prophylaxis drugs are required to reduce the health burden placed on allo-HCT recipients. In this review, we will summarize the emerging concepts revolving around three biologic-based therapies for GVHD using T regulatory cells (Tregs), myeloid-derived-suppressor-cells (MDSCs) and mesenchymal stromal cell (MSC) exosomes. This review will highlight how each specific modality is unique in its mechanism of action, but also share a common theme in their ability to preferentially activate and expand Treg populations in vivo. As these three GVHD prevention/treatment modalities continue their path toward clinical application, it is imperative the field understand both the biological advantages and disadvantages of each approach.